Variation in the reported management of canine prolapsed nictitans gland and feline herpetic keratitis - White, Constance; Jones, Gareth; Baker, Sarah; Dean, Rachel; Brennan, Marnie (MDPI, 2018)
Treatment variation in medicine may be driven by evidence gaps, clinician factors, and patient preferences. Although well-documented in human medicine, variation in clinical management is relatively unexplored in veterinary practice. Clinical vignette questionnaires were administered to a cross section of general practitioners (GPs) and veterinarians with postgraduate training in ophthalmology (PGs) to survey recommended management of canine prolapsed nictitans gland (“cherry eye”, PNG) and feline herpesvirus (FHV-1) keratitis. The majority of veterinarians (96.2%) suggested surgical replacement of cherry eye, with a pocketing technique being the most frequently nominated procedure. GPs were more likely to suggest gland excision in the event of surgical failure, while PGs more frequently nominated techniques incorporating a periosteal anchor for salvage repair. Most respondents managed FHV-1 keratitis with topical antibiotics (76.4%), with a minority suggesting topical antivirals (32.2%). GPs favoured topical acyclovir whilst PGs more frequently recommended topical trifluorothymidine. A significantly larger proportion of PGs nominated systemic famciclovir and lysine supplement for FHV-1 keratitis. This survey revealed moderate treatment variation for these conditions, both between and within practitioner groups. Additional research is needed to assess the reasons for this variation, particularly for conditions in which high quality evidence is scant.